MRI-based quantification of adipose tissue distribution in healthy adult cats during body weight gain - Del Chicca, Francesca; Richter, Henning; Müller, Hans-Peter; Kassubek, Jan (Frontiers in Veterinary Science, 2023)
The incidence of obesity in pet population increased over the last decades. Cats have been suggested as model for human obesity because of similar co-morbidities as diabetes and dyslipidaemia. Aim of this study were to quantify the distribution of visceral and subcutaneous adipose tissue (VAT, SAT respectively) in healthy adult cats during feeding-induced body weight (BW) gain by MRI, and to correlate it to the increased hepatic fat fraction (HFF). Cats received a commercial dry food ad libitum for 40 weeks and were longitudinally scanned three times. VAT and SAT were determined from Dixon MRI data by a dedicated software solution (ATLAS, established in human and rodents). HFF was quantified from a commercially available sequence. At both individual and group level, normalized adipose tissue volumes significantly increased longitudinally, with median VAT/SAT ratio always <1. With increased BW, more than proportional increased total adipose tissue was observed together with more than proportional increased HFF. HFF is disproportionately high in overweight cats compared to SAT and VAT accumulation in the 40 weeks observation period. Quantitative unbiased MRI examination of different body fat components is useful in longitudinal monitoring of obesity in cats.